EI24, as a Component of Autophagy, Is Involved in Pancreatic Cell Proliferation - Hwang, Mihwa; Jun, Dong Wha; Kang, Eun Hye; Yoon, Kyong-Ah; Cheong, Heesun; Kim, Yun-Hee; Lee, Chang-Hun; Kim, Sunshin (Frontiers in Oncology, 2019)
Autophagy is a highly conserved cellular process in which cytoplasmic materials are degraded and recycled as energy sources when nutrient supplies are lacking. Established tumor cells require autophagy for cell growth and tumor promotion. In particular, the survival of pancreatic tumor cells appears to be strongly dependent on autophagy, referred to as autophagy addiction. This dependency of pancreatic tumor cells on autophagy may be a candidate target for pancreatic tumor therapy. EI24 (etoposide-induced gene 2.4-kb; PIG8, p53-induced gene 8) acts as a tumor suppressor, inhibiting cell growth and inducing apoptosis in breast, cervical and prostate cancer cells. However, recent papers have reported that EI24 is an essential component of the autophagy pathway. This newly discovered role of EI24 as a component of autophagy may act as a tumor promoter, which is contradictory to its known role as a tumor suppressor. We investigated the role of EI24 as a component of autophagy in pancreatic tumor cell proliferation. Here, we demonstrated that knockdown of EI24 using siRNA in pancreatic tumor cells led to impaired autophagy at a late step (increase in LC3-II and accumulation of p62 and autolysosomes). EI24 deficiency in pancreatic tumor cell lines inhibited cell proliferation. We confirmed that loss of EI24 inhibited pancreatic cell proliferation using the CRISPR-Cas9 system. However, loss of EI24 in other cell lines did not affect cell proliferation. Taken together, our results suggest that EI24 acts as a tumor promoter in pancreatic tumor cells, and studying the role of EI24 in reference to its cellular context may lead to a useful therapeutic target.